2015
DOI: 10.1371/journal.pone.0144069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Change in Working Status on the Health of Older People in Japan

Abstract: BackgroundWorking at old ages is regarded as a good way to keep one’s health according to the idea of productive aging. However, there is not enough evidence yet whether retirement is good or bad, or the kind of effects it has on the health of older adults aged 65 and over. We examined it by using a recent data of Wako city, a suburb area near Tokyo in Japan.MethodsOne thousand seven hundred sixty-eight participants answered to 3 waves of survey questionnaires: 2008, 2010, and 2012, successively. We considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 17 publications
4
74
0
1
Order By: Relevance
“…This is the first longitudinal study to compare work with other community organizations by defining work as a type of social participation. Previous longitudinal studies focusing on the relationship between work and health outcomes among older people have examined work alone [20,36,37], and comparisons with other community organizations have been cross-sectional studies [38]. Given the current challenges posed by a rapidly declining birthrate and aging population, it is necessary to develop a social structure where many older people work [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first longitudinal study to compare work with other community organizations by defining work as a type of social participation. Previous longitudinal studies focusing on the relationship between work and health outcomes among older people have examined work alone [20,36,37], and comparisons with other community organizations have been cross-sectional studies [38]. Given the current challenges posed by a rapidly declining birthrate and aging population, it is necessary to develop a social structure where many older people work [39].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that working support and improvement of working environment could be public health policies that would prevent the need for the provision of long-term care in rural and urban areas. In longitudinal studies of work and health outcomes [20,36,37], work is generally considered good for health. However, poor-quality work [36] is not good for health; therefore, additional analysis is necessary, since this research did not consider the type of work.…”
Section: Discussionmentioning
confidence: 99%
“…One important finding of this study was a significant reduction in BP and HR by regular laughter intervention (Figure a,b). This reduction is considered to be induced by parasympathetic activation followed by relaxation and reduced stress by laughter therapy, because early reports demonstrated that humorous stimulation by a funny movie or happy laughter had a beneficial influence on physiological responses determined by BP and HR via autonomic responses (Minami et al, ; Nezu, Nezu, & Blissett, ). Reduced stress by laughter therapy was also confirmed by lowered levels of stress hormones in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We observed older people in urban areas working in paid and unpaid roles in shops, restaurants, religious shrines and tourist centres. In rural areas older peoples' work involves farming and fishing (Minami et al 2015). Unemployment is associated with worse health outcomes in both European and East Asian states (Chuang et al 2011).…”
Section: The Role Of Workmentioning
confidence: 99%
“…Rapid cultural changes in Japan have seen the position of older people change from traditionally expected 'withdrawal from life' and dependency within family-orientated care based on values of filial responsibility, to that of 'active ageing', more nuclear families, flexible approaches to eldercare and the role of older family members as a form of 'safety net' in an economic crisis (Wilinska and Anbacken 2013). Minami et al (2015) found that retirement had a damaging effect on both mental health and activities of daily living and suggested that work of any form has health promoting benefits, mainly due to its impact on social inclusion. In Japan voluntary work is currently promoted through rewards including vouchers and holidays, while future policy will promote work opportunities as central to a range of solutions designed to encourage social participation (Minami e al 2015).…”
Section: The Role Of Workmentioning
confidence: 99%